Structural change and generalized balanced growth - Jürgen Meckl (Universität Konstanz, Fachbereich Wirtschaftswissenschaften, 1999)
This paper addresses the criticism that balanced growth models are inconsistent with the dynamics of structural change typical for the process of economic growth. Using a sectoral disaggregated version of a researchdriven growth model, we develop the concept of a generalized balanced growth path (GBGP). The GBGP preserves decisive properties of the balanced growth path analyzed in aggregated growth models. Along a GBGP, aggregate variables grow at constant rates (balanced growth) while disaggregated variables grow at non-constant rates. The aggregated model's implications for the behavior of aggregates are robust with respect to structural dynamics.
Keywords: O14; O41; 330; structural adjustment; innovation-based growth